Effects of early trauma and corticotropin‐releasing factor receptor 1 gene polymorphism on adult visual spatial memory. Issue 12 (22nd October 2019) - Sun, Fei‐Fei; Wang, Ran; Li, Na; Zhao, Xiao‐Chuan; Wang, Lan; Song, Mei; Yu, Lu‐Lu; Chen, Ya‐Nan; An, Cui‐Xia; Wang, Xue‐Yi
Abstract: Background: The study sought to determine the effects of earthquake on the working memory of adults who experienced earthquake either as infants or fetuses and also investigates whether earthquake exposure and corticotropin‐releasing factor receptor 1 ( CRHR1 ) variants rs242924 and rs7209436 interacted with each other in modulating working memory. Methods: We enrolled subjects who experienced the Tangshan Earthquake as fetuses (group I) or infants (group II), as well as those who did not experience the earthquake (group III). Their working memory was measured using Brief Visuospatial Memory Test‐Revised (BVMT‐R) and Hopkins Verbal Learning Test‐Revised (HVLT‐R). Two single‐nucleotide polymorphisms (SNPs) of CRHR1 rs242924 and rs7209436 were analyzed by fluorescence quantitative polymerase chain reaction (PCR). Results: The study enrolled 535 subjects, including 172 subjects in group I, 176 subjects group II, and 187 subjects in group III. Both group I and II had significantly lower BVMT‐R scores than group III ( p < .05). Moreover, no difference was observed in HVLT‐R scores among the three groups ( p > .05). The allele frequency was 84.7% for AA, 82.8% for TT, 13.6% for AC, and 15.9% for TC. C gene carriers in group II ( t = −4.231, p < .01) and group I ( t = −3.201, p < .05) had significantly lower visual spatial memory scores than group III. Furthermore, AT gene carriers had significantly lower visual spatial memory scores than C gene carriers in group III ( t = 2.215, p < .05). Moreover, there was significant interaction between earthquake exposure and CRHR1 genotype in their effects on visual spatial memory ( F = 4.028, p < .05). Conclusions: Our cross‐sectional study has demonstrated that infant or fetus exposure to earthquake impairs visual spatial memory during adulthood and CRHR1 polymorphisms and earthquake exposure may interact with each other to accentuate this impairment. Abstract : Our cross‐sectional study has demonstrated that infant or fetus exposure to earthquake impairs visual spatial memory during adulthood and CRHR1 polymorphisms and earthquake exposure may interact with each other to accentuate this impairment.